Commercial Feed Diluted with Different Fiber Sources and Enzyme Product for Broilers: Growth Performance, Carcass and Gut Health - SS Diarra; S Anand; T Lemuelu; F Areta; E Mathew; E Lehi; S Hoponoa; F Kava; J Mafi; F Taliauli (Brazilian Journal of Poultry Science, 2022)
ABSTRACT The dilution of commercial broiler feed with copra meal (CM), palm kernel meal (PKM) and cassava leaf meal (CLM) and enzyme supplementation was investigated. Two hundred and eighty 7-day old Cobb 500 broilers were fed commercial feed alone or diluted with the test ingredients with and without enzyme. There were no interaction effects (p>0.05) on feed intake (FI) and weight gain (WG). Poorer (p<0.05) feed conversion ratio (FCR) was observed on the diet diluted diets from 22-42 d, but this was restored (p>0.05) by enzyme supplementation. There was no interaction effect on final body weight (FBW). Diet dilution depressed FBW (p<0.05) but enzyme supplementation restored (p>0.05) this weight depression. Abdominal fat was lighter (p<0.05) on CLM compared to CM. There were no interaction effects (p>0.05) on the weight of gut segments and E. coli count. Heavier (p<0.05) liver, gizzard and intestine were observed on the test diets. Commercial feed dilution with CM, CLM and PKM at 100 g/kg for starter and 200 g/kg for finisher would be a viable option for smallholder broiler production. More research is needed into dilution levels and enzyme concentrations.